Developments in International Trade Policy - Kirmani, Naheed (Occasional Papers; Occasional Paper ;, 1982)
This paper contains further work by the Fund staff on trade issues and developments following the pattern of the surveys prepared in 1978 and 1981, mainly focusing on commercial policies of the major trading nations. It also includes a discussion of agricultural protection and issues relating to international trade in agricultural products.